PENGARUH TINGKAT KETEBALAN MULSA JERAMI DAN SEKAM PADI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA MERAH (Lactuca sativa var. crispa) - Herlina, Ninuk; Kelana, Muhammad (Universitas Islam Kadiri, 2024)
Lettuce vegetable production increased during 2015-2018, but there are several cultivation constraints, especially in the lowlands, which can result in decreased crop quality. The use of mulch, particularly rice straw and rice husk, was identified as an imporplantt strategy to increase and maintain soil moisture. Rice straw mulch and rice husk, not only inhibits weed growth, but also increases the value of agricultural waste, and contains soil organic matter. The aim of this study is to investigate and undersplantd the impact of different levels of straw and rice husk mulch thickness on the growth and yield of red lettuce plants. The research was conducted from March to May 2024. The research was carried out in Pandanwangi sub-district, Blimbing District, Malang City, East Java Province. The research was conducted using a non-factorial design method and was designed using a Randomized Block Design. The research consisted of 7 treatments and was repeated 4 times. The results showed that the 6 cm rice husk mulch treatment gave higher plant height, number of leaves and dry weight compared to the treatment without mulch. The treatment of 4 cm thick rice straw mulch and 6 cm rice husk produced fresh weight of consumption of 15.25 and 17.26 t ha-1, respectively, 24.49 and 40.89% higher than the treatment without mulch.